The changing nature of work and earnings inequality in China - Chunbing Xing (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
This paper examines the evolution of China's industrial and occupational structure in the last two decades and its impact on wage inequality. We find that non-routine cognitive and interpersonal tasks have increased, while routine cognitive tasks first increased and then declined. Occupation structural change is accompanying rising wage inequality. The wage premium for educated workers rose sharply in the 1990s and remained high thereafter. Occupations with high routine task intensity are associated with lower wages. While the return to education has become the largest contributor to wage inequality, routine task intensities have yet to play a significant role.
Keywords: I32; O14; O15; P23; 330; occupational structure; inequality; education; China